APLIKASI HASIL PENELITIAN PENDAMPINGAN KADER DAN KELUARGA TERHADAP TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG KUNJUNGAN ANTENATAL SERTA TES HIV - Dina Indrati Dyah Sulistyowati (Jurnal Salingka Abdimas, 2022)
Abstract Background: Each year it is estimated that more than 800,000 babies become infected with HIV as a result of mother-to-child transmission. If there are no precautions, there will be 3000 babies who are feared to be born HIV positive every year in Indonesia. One of the government's efforts is a program to prevent HIV transmission from mother to child, namely with HIV testing mandatory to offer to all pregnant women. The purpose of this community service is to find out how the application of Social Support Care Motivator: Assistance of Cadres and Maternal Affection Families on the Level of Knowledge and Attitudes of Pregnant Women About Antenatal Visits and HIV Test Recommendations in Purwokerto region". and analyze differences in the level of knowledge and attitudes of pregnant women about the government program of HIV/aids testing after training and assistance to pregnant women in the community. Methods and Partners: This community service method is by organizing training motivators Social Support Care: Cadre and Family Assistance for pregnant women. Implementation of service in collaboration with the Banyumas Health Office as well as cadres Benefits: The results of this community service are expected to be an operational standard in helping to improve the treatment and attitudes of pregnant women towards antenatal visits and HIV testing. Result: Community Service Motivator Social Support Care: mentoring cadres and families of maternal affection can increase the knowledge and attitudes of pregnant women about the transmission of HIV / AIDS transmission in children. In addition, cadres can play an active role in improving the health of pregnant women and preventing risks to pregnant women. Keywords: Motivator of social support Care: Cadre Assistance, Knowledge, Attitude, Pregnant Women